Investigation of the Effect of Skate-Useon the Sole Contact Areas and Maximal Forces of Ice Hockey Players - Ahmet Uzun; Erdinç Esen; Latif Aydos; Metin Kaya; Ulunay Kanatlı (Türk Spor ve Egzersiz Dergisi)
The aim of the present study was to compare the pedobarographic parameters of contact areas and maximal forces for 11 contact areas of foot-soles in professional male Ice hockey players and healthy people and to investigate the effect of Ice hockey on the foot-sole. The study consisted of 22 Ice hockey players without any foot-related complaints and as the control group, 25 male volunteers.  EMED-SF plantar pressure analysis system was used in the study. Any statistically significant difference between the averages of the study and the control groups was examined using non-parametrical Mann Whitney U test and the extent of the linear relationship between the physical structure and the variables of the foot-sole was examined by calculating the Pearson (r) coefficient. According to these results and after the measurements on foot-sole variables and the sports done by the ice hockey players; a significant difference between right foot heel lateral and left foot 4th metatarsus head in terms of 11 contact areas. As for the maximal forces of the contact areas; it was found out that the difference between left foot total, 2th metatarsus head and pollex was found to be significant (P lt;0.01-0.05). As a result; ice hockey caused some changes in contact areas of the foot-sole and maximal forces of the contact areas, but it did not cause big damages for the foot-sole. It was particularly seen that shoes worn were partly successful in supporting and protecting foot-sole. As the result of these conclusions; it was concluded that ice hockey did not cause such a serious damage to foot-sole of the players to require medical interventions.